Effects of Hematoma Reduction by Stereotactic Aspiration for Patients With Spontaneous Intracerebral Hemorrhage. Issue 1 (February 2015) - Chung, Tzu-Tsao; Hsieh, Cheng-Ta; Chen, Yuan-Hao; Chang, Cheng-Fu
<x xml:space="preserve">Abstract</x> Background/Purpose: Spontaneous intracerebral hemorrhage (ICH) is a devastating medical condition associated with significant morbidity and mortality. Whether the hematoma should be surgically removed remains controversial. This study was a retrospective analysis of patients with spontaneous ICH who were treated with computed tomography (CT)-guided stereotactic aspiration. The aim of this study was to investigate whether hematoma volume reduction in deep-seated ICH utilizing this minimally invasive surgical procedure improves clinical outcome. Methods: Ninety-nine patients who suffered spontaneous ICH provided informed consent and were included in the study. Patients were divided into an operated group that underwent CT-guided stereotactic aspiration, and a nonoperated group that received only medical treatment. CT-guided stereotactic aspiration was performed at least 8 hours after onset of ICH. Using the Leksell stereotactic frame for guidance, a 4-mm-diameter catheter was inserted into the body of the hematoma through a frontal burr hole. Glasgow Coma Scale, motor function, and length of hospital stay were used to assess differences in outcomes between the 2 groups. The correlation between clinical outcome and stereotactic aspiration was evaluated using multivariate regression analysis. Results: Ninety-nine consecutive patients were entered into this study. Patients in the operated group (n=41) were treated with CT-guided stereotactic hematoma aspiration. The 3-month Glasgow Outcome Scale score in the nonoperated group (n=58) was significantly lower than that in the operated group (2.32±1.26 vs. 3.15±1.33, P<0.001). Patients in the operated group experienced greater motor function recovery than those in the nonoperated group. The average length of hospital stay of the operated group was significantly shorter than that of the nonoperated group (31.2±14.6 vs. 41.7±17.2 d, P=0.002). Conclusions: Stereotactic aspiration may improve the functional outcome and shorten the hospital stay of patients who have suffered spontaneous ICH. This procedure is minimally invasive and shows promise as a safe and effective treatment method for these patients.